Comparing Determinant of Profitability Between Islamic Banks and Conventional Banks in Indonesia Case Study Eight Islamic banks and Eight Conventional Banks in Indonesia Period 2010 - 2013 - Herdiana, Dita; Aliludin, Arson (Journal of Business and Management, 2014)
The main theme of this research is profitability and focus on finding determinant profitability in Islamic banking. It also explain the differences determinant of Islamic banking and conventional banking in Indonesia. This research uses quarterly bank’s financial report from July 2010 until September 2013 from 8 Islamic banks and 8 conventional banks. The sample selections from Islamic banks are 3 non foreign exchange banks and 5 foreign exchange banks; and, the sample from conventional banks are 1 non foreign exchange bank, 2 state owned banks and 5 foreign exchange banks. This research used multiple regression method as analysis statistic tools to determine which factors affect each dependent variable. The dependent variables are Return on Asset (ROA), Return on Equity (ROE) and Net Interest Margin (NIM). The independent variables from Islamic banks are IB wadiah demand deposit, IB wadiah saving deposit, IB mudharaba saving deposit, IB total saving deposit, IB mudharaba time deposit and IB total depositors funds, mudharaba receivable, placement in Bank Indonesia, placement in other banks, security in investment, then small enterprise credit, non-small enterprise credit, property credit, non-property credit, quick ratio and core depositors to depositors funds ratio. The independent variables for conventional banks are demand deposit, saving deposit, time deposit, cash, placement in Bank Indonesia, placement in other banks, security in investment, small enterprise credit, non-small enterprise credit, and restructured credit property credit. The result showed the independent variables that significantly affects ROA is IB wadiah demand deposit for Islamic banks and demand deposit for conventional banks; the independent variables that significant variable with ROE is IB wadiah demand deposit for Islamic banks and demand deposit for conventional banks; and the independent variables that significant variable with NIM is IB mudharaba time deposit for Islamic banks and time deposit for conventional banks. This research shows depositors’ funds have significant effect for ROA, ROE and NIM. Keywords: Islamic Banking, Conventional Banking, Depositors Funds, Profitability, Multiple Regressions